2021
DOI: 10.1002/imhj.21952
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ and toddlers’ digital media use and mothers’ mental health: A comparative study before and during the COVID‐19 pandemic

Abstract: This study compared children's and mothers’ digital media use and mothers’ mental health in two samples: one accessed before (Group 1; N = 257; M = 33.18 years; SD = 4.79) and the other accessed during (Group 2; N = 256; M = 33.51 years; SD = 4.96) the COVID‐19 pandemic in Brazil. Mothers of children up to 3 years old (Group 1: M = 17.95 months, SD = 9.85; Group 2: M = 16.48 months, SD = 10.15) answered an online survey. Bivariate analysis, factorial ANOVA tests, and multiple linear regression were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 88 publications
(118 reference statements)
1
8
0
3
Order By: Relevance
“…First, we found that child screen time significantly changed between the pre-lockdown period, the three lockdowns and the post-lockdown period. Replicating findings from recent studies ( Bergmann et al, 2022 ; Carroll et al, 2020 ; Eales et al, 2021 ; Pedrotti et al, 2022 ; Ribner et al, 2021 ), screen time increased and remained stable during lockdowns compared with the pre-lockdown period. Unexpectedly, screen time further increased in the post-lockdown period, suggesting that the disruption caused by lockdown routines may have changed habitual child viewing habits.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…First, we found that child screen time significantly changed between the pre-lockdown period, the three lockdowns and the post-lockdown period. Replicating findings from recent studies ( Bergmann et al, 2022 ; Carroll et al, 2020 ; Eales et al, 2021 ; Pedrotti et al, 2022 ; Ribner et al, 2021 ), screen time increased and remained stable during lockdowns compared with the pre-lockdown period. Unexpectedly, screen time further increased in the post-lockdown period, suggesting that the disruption caused by lockdown routines may have changed habitual child viewing habits.…”
Section: Discussionsupporting
confidence: 72%
“…Research on adult samples shows that between 49 and 70% of adults reported spending more time using screens during this period ( Górnicka et al, 2020 ; Pišot et al, 2020 ). An emerging body of literature suggests a similar increase among young children ( Bergmann et al, 2022 ; Carroll et al, 2020 ; Eales et al, 2021 ; Pedrotti et al, 2022 ; Ribner et al, 2021 ). For example, in a study focused on children under the age of 6 years living in Canada, parents reported that since the COVID-19 outbreak 87% of children increased recreational screen use ( Carroll et al, 2020 ).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Parents are encouraged to create and maintain healthy structured routines including sleep schedules and family media plans that foster the healthy use of recreational mobile devices (e.g., limits on duration). However, interventions focusing on reducing infants' and toddlers' screen time should be more targeted to parents, particularly parental mental health, screen time, intention to offer mobile devices to children and the needs of using mobile devices ( 92 ). Furthermore, since physical activity is associated with psychological health, promoting physical activities that can be performed in a limited space at home should be highly recommended to better support the psychological health of children.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most reported consequences of the COVID-19 restrictions has been increased screen time among adults [ 5 , 6 ], children and adolescents [ 7 , 8 , 9 , 10 , 11 , 12 ], and even toddlers [ 7 , 13 ]. Systematic reviews have also concluded that mental health problems (e.g., anxiety, depression, and stress) increased among adolescents during the pandemic [ 3 , 14 ].…”
Section: Introductionmentioning
confidence: 99%